Perbandingan Struktur Biaya dan Pendapatan Usahatani Sawi Pakcoy (Brassica chinensis L.) Metode Hidroponik dan Konvensional di Kota Jambi - Nida Kemala; Mulyani Mulyani; Agil Ahmad Falah (Universitas Batangahari Jambi, 2022)
This research was conducted on hydroponic system and conventional system of mustard pakcoy farming in Jambi City. The study used a survey method, while the data collected came from primary and secondary data. The type of data based on time used cross section data and was ratio. This study aimed to describe the proportion of costs, to analyze the difference in costs proportion and the difference in farming income of pakcoy mustard between hydroponic and conventional method. The number of sampling method used in this study were two types, namely snowball and proportional random sampling. Samples for hydroponic pakcoy mustard farmers were determined sequentially using the snowball sampling technique and obtained 5 farmers. Meanwhile, the sample of conventional pakcoy mustard farmers was determined by proportional random sampling with a sample of 40 farmers. The analytical tool used to see the difference in the proportion of cost structure was the Z-test of different proportions and to see the difference of income, the analysis tool was used a Z-test the difference of two large sample averages (n1/n2 greater than 30 and unpaired) where the population variance was unknown. The results showed that the fixed cost of hydroponic mustard farming was Rp. 321.318/period with a proportion of 0.17%, while the fixed cost of the conventional method was Rp. 55,892.53/period with a proportion of 15.99%. It showed a contrary with the proportion of variable costs that was greater in conventional farming (84.01%) than then hydroponics one (83%). There was a significant difference between the costs proportion, both fixed costs and variable costs between hydroponic and conventional methods. Likewise, the income between these two methods also showed a significant difference.